PERAN MBKM INTERNAL DALAM MENJEMBATANI KESENJANGAN KURIKULUM TERHADAP KEBUTUHAN INDUSTRI: STUDI KASUS PROGRAM MBKM DI STIE WIYATAMANDALA - Angelita, Angelita; Kuswanto, Randy (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This study aims to explore the perceptions of STIE Wiyatamandala final students on the influence of the internal MBKM program, Wiyatadharma in bridging the gap in curriculum suitability to industry needs. This study applied a quantitative data-based approach of moderated regression analysis. Potential respondents in this study reached all final year students of STIE Wiyatamandala with a total sample of 65 students. The steps in data collection in this study used an online questionnaire. The test results prove: (1) the relationship between curriculum suitability, the role of internal MBKM, and their interaction on the dependent variable is not statistically significant. (2) the direct effect of curriculum suitability on the dependent variable is very weak and insignificant. (3) the effect of internal MBKM role on the dependent variable is very small and statistically insignificant. (4) the moderating effect of the role of internal MBKM on the relationship between curriculum suitability and industry needs is not significant. This research data indicates that the relationship between variables in this model is not strong, so it requires further review. Efforts that can be made include re-testing data quality, identifying other potential variables that might moderate the relationship, or exploring other more complex analytical approaches to understand variable relationships